ANALYSIS OF THE TRANSMISSION RELIABILITY BETWEEN CONTROL SYSTEMS DEVICES WHEN ERRORS ARE PACKAGED - Freyman, V. I. (Radio Electronics, Computer Science, Control, 2019)
Context. The reliability indicators of information transmission between control systems elements, taking into account the packaging (grouping) of errors in the communication channel, are analyzed. The research object are the characteristics and parameters of noise stability cyclic binary and non-binary codes for the correction of error packets. The research subject is a theoretical and experimental comparative analysis of the reliability indicators of codes for correcting error packets. Objective. The purpose of the work is to determine the analytical dependencies of the reliability indicators of the selected redundant codes from their parameters and the communication channel properties develop models for their experimental research, formulate recommendations for choosing codes with preset characteristics with certain properties, and an error description model. Methods. The math methods and building theory of noise stability cyclic binary (BCH) and non-binary (Reed-Solomon) codes are used. The analytic formulas for determination of reliability indicators taking into account bits distortions within error packet are received. The dependencies for corrective properties and correct transmission probability form codes and error parameters are researched, the illustrating examples are shown. The simulation circuit design models for control systems with researched methods of noise stability encoding are developed. The experimental research has been done, based on the results, conclusions and recommendations for choice of code parameters for preset reliability indicators for providing of maximum efficiency (information rate) are made. Results. The dependencies of the reliability indicators (correct transmission probability) and the corrective properties (the length of corrected errors packet) from its parameters (the number of redundancy symbols, the interleaving degree – for BCH-codes; the Galua field module, number of corrected errors – for Reed-Solomon codes) are received. The recommendations of using the received results for code parameters choice are given. Conclusions. The performed researches allows calculate and reasonably choose of redundancy codes parameters for preset reliability indicators и the behavior model of errors within the communication channel. It makes possible to design and implement reliable control systems with preset reliability indicators and maximum information rate.